Indoor air quality and self-reported multiple chemical sensitivity in newly constructed apartments in Indonesia. (4th March 2021) - Kubota, Tetsu; Sani, Hanief Ariefman; Hildebrandt, Sophia; Surahman, Usep
Abstract : There is a possibility that sick building syndrome has already spread widely among newly constructed residential buildings in developing countries. This study investigates the current conditions of IAQ and their effects on health among occupants in two representative types of residential buildings in Jakarta and Surabaya: high-rise apartments and traditional landed houses. A total of 707 respondents were interviewed and 125 rooms were measured during 2017–2018. The results indicated that approximately 40–50% of the respondents in the newly constructed apartments showed some degrees of MCS risk. Formaldehyde and TVOC concentrations in apartments were especially critical. Furthermore, the respondents with a higher MCS risk were found to be exposed to increased TVOC concentrations in the apartments. Other than the IAQ, higher levels of stress are probably one of the most influential factors, followed by gender (females), occupation, window-opening, frequency of cleaning, the prevalence of allergic diseases and possession of AC.